Conscious thinking. (Economist, 2023)
The article discusses a gathering of experts attempting to track how consciousness is generated in the brain and identify which other animals might possess it. Topics include the examination of two hypotheses, the absence of clear neural correlates of consciousness, and the exploration of consciousness in vertebrates, cephalopods and arthropods.